Epoxidation reaction in promising Brazilian biomass: decreased time and catalyst loading to produce renewable monomers - Magri, Raquel [UNESP]; Gaglieri, Caroline [UNESP]; Alarcon, Rafael T. [UNESP]; Bannach, Gilbert [UNESP] (Springer Nature, 2021)
The syntheses of new materials using vegetable oils have increased due to technological interest and low environmental impact. Baru nut provides baru oil, rich in linoleic and oleic fatty acids that can be modified into epoxides compounds. Thus, the optimization of the epoxidation synthesis of baru vegetable oil by the conventional thermal route was investigated using green and quick heterogeneous catalytic method. The raw baru oil and epoxidized oil were characterized by titrimetric, spectroscopic, and thermal analyses. Here we demonstrate that the epoxidation of baru oil does not require 6 h or 25% of catalyst as reported in the literature. However, it was possible to achieve ≥ 99% of alkenes conversion into epoxide rings in just 3 h of reaction with 10% of heterogeneous catalyst.
Keywords: Baru oil; Green chemistry; Heterogeneous catalyst; Optimization process